Simulation of an anti-sloshing technique using floating foams based on the moving particle semi-implicit method—The discrete element method algorithm - Geng, Chong; Wang, Wen-Hua; Piao, Tai-Wei; Chen, Yu-Qing; Heng, Meng-Yuan; Zhou, Zi-Qi; Yu, Xue-Jie; Huang, Yi (Physics of fluids (1994), 2024)
The moving particle semi-implicit (MPS) method can simulate nonlinear, large-deformation fluid flows, and the discrete element method (DEM) is effective in modeling the interaction of solid bodies. Therefore, it is feasible to simulate the influence of floating foam balls on sloshing by establishing the coupling effect between solid and liquid phases. In this study, the MPS method, with an improved source term and the optimized DEM, is verified by simulations of sloshing and solid-body movements, respectively. The proposed coupling algorithm behaved with acceptable performance in the simulation of the dam break scenario involving multiple layers of solid cylinders. The sloshing numerical tests with floating foams are carried out to demonstrate the accuracy of the MPS-DEM coupling algorithm when the transient behavior is compared.